Effects Of Deforestation And Afforestation In The Central Part Of The East European Plain On Regional Weather Conditions - Mikhail A. Nikitin; Ekaterina V. Tatarinovich; Inna A. Rozinkina; Andrei E. Nikitin (Geography, Environment, Sustainability)
Forest vegetation can affect the climate and weather patterns in multiple ways. What are the main mechanisms of such influence and how the land-use and vegetation changes may affect the weather and climate conditions in different geographical regions are still not quite clear. In our study, the possible impact of land use and forest cover changes in the central part of the East European plain on regional meteorological conditions was investigated using the regional COSMO model. In our modeling experiments we used two extreme land-use change scenarios imitating total deforestation and afforestation of experimental area located between 55° and 59ºN and 28° and 37°E in the central part of the East European plain. Modeling results conducted for the year 2016 showed that deforestation results in increase of the temperature difference between summer and winter months by up to 0.6ºС and in reduction of the annual precipitation by 35 mm. On the contrary, afforestation leads to decrease of the annual temperature range by 0.3° С and to growth of annual precipitation by 15 mm. Moreover, the deforestation results in higher frequencies of stronger winds and lower number of fog events, while the afforestation leads to opposite effects. Analysis of the Khromov and Gorchinsky indexes of continentality showed that the deforestation of the selected experimental area may lead to increase of the climate continentality in the study region, whereas the afforestation results in milder climate conditions.